Retrospective analysis of Stevens-Johnson syndrome and toxic epidermal necrolysis over a period of 10 years - Abarna Devi Sanmarkan; Tukaram Sori; Devinder Mohan Thappa; T J Jaisankar (Wolters Kluwer Medknow Publications, 2011)
Background: Stevens-Johnson syndrome (SJS), and toxic epidermal necrolysis (TEN), are the acute emergencies in dermatology practice. Prompt diagnosis and management may reduce the morbidity and mortality in SJS/TEN patients. Early identification of the offending drug is necessary for early withdrawal and to prevent the recurrences of such a devastating illness. Aims : To study the demography, offending agents, clinical and laboratory features, treatment, complications, morbidity and mortality of SJS/TEN in our hospital. Materials and Methods: In this retrospective study, we reviewed the medical records of SJS, TEN, SJS/TEN overlap of inpatients over a period of 10 years Results: Maximum number of SJS/TEN cases were in the age group of 11-30 years. Males predominated in the SJS group with a ratio of 1.63:1, whereas females predominated the TEN group with a ratio of 1:2.57. Nonsteroidal anti-inflammatory drugs (NSAIDs) were the commonest group of drugs among the SJS group in 5/21 patients (23.8%). Antimicrobials were the commonest group of drugs causing TEN in 11/25 patients (44%). Mucosal lesions preceded the onset of skin lesions in nearly 50%. Our study had one patient each of SJS/TEN due to amlodipine and Phyllanthus amarus, an Indian herb. The most common morbidity noted in our study was due to ocular sequelae and sepsis leading to acute renal failure respectively. Kaposi's varicelliform eruption was found in three of our patients. Conclusion: Antimicrobials and NSAIDS are the common offending agents of SJS/TEN in our study.